Primary school healthy lifestyle promotion: preventing childhood obesity and overweight through a participatory action research project - De Luca, Enrico; Menta, Lorena; Carrieri, Angela; Bonetti, Marianella; Papa, Martina; Vetri, Giancarlo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2025)
Background. In the last 30 years, childhood obesity has become a global issue. In Europe, Italy is particularly affected, especially among primary school-aged children. Post-COVID-19 reflections revealed the need for more research and collaboration to address this concerning issue for children health.  Aims. To understand parents, teachers, and healthcare professionals’ childhood obesity and overweight perceptions and to co-create an educational intervention. Methods. A participatory research approach, combined with qualitative methods, was based on a high child obesity rate area of Southern Italy. Results. Focus groups conducted in three primary schools involved teachers, parents, and healthcare professionals. The emerging themes, “Healthy lifestyle: a complex issue?”, “Fat Stigma and Prejudice” and “Possible Interventions”, paint a dramatic scenario and highlight that obesity prevention is effective only through the integrated involvement of all parties and the community playing a central role. Sharing results with stakeholders helped to draft prospective education interventions. Conclusion. Collaboration between public and private parties and avoiding a blame culture by listening to the needs of families and children is crucial in preventing childhood obesity and overweight.